2022
DOI: 10.1111/jam.15649
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing rhizobacteria to fulfil inter-linked nutrient dependency on soil and alleviate stresses in plants

Abstract: Plant rhizo-microbiome comprises complex microbial communities that colonize at the interphase of plant roots and soil. Plant growth-promoting rhizobacteria (PGPR) in the rhizosphere provide important ecosystem services ranging from the release of essential nutrients for enhancing soil quality and improving plant health to imparting protection to plants against rising biotic and abiotic stresses. Hence, PGPR serve as restoring agents to rejuvenate soil health and mediate plant fitness in the facet of changing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 186 publications
1
1
0
Order By: Relevance
“…The results reported in this work are also in alignment with agricultural studies pertaining to the root bed in plants showing heavy presence of certain microbes “seed to rhizo-micro-biomes”( Neemisha et al, 2022 ; Orozco-Mosqueda et al, 2022 ) which dominate plant growth ( Chang et al, 2022 ; Zhang et al, 2020 ), rigor, fitness, and crop yield ( Abdullaeva et al, 2021 ) Koprivova and Kopriva, 2022 ; Li et al, 2022 ). Microbial communities residing in roots are diverse, some including non – pathogenic B. cereus group, and spp of Enterobacter, Pseudomonas, Cronobacter , with those close to water having the greatest diversity ( Sun et al, 2019 ).…”
Section: Rootssupporting
confidence: 83%
“…The results reported in this work are also in alignment with agricultural studies pertaining to the root bed in plants showing heavy presence of certain microbes “seed to rhizo-micro-biomes”( Neemisha et al, 2022 ; Orozco-Mosqueda et al, 2022 ) which dominate plant growth ( Chang et al, 2022 ; Zhang et al, 2020 ), rigor, fitness, and crop yield ( Abdullaeva et al, 2021 ) Koprivova and Kopriva, 2022 ; Li et al, 2022 ). Microbial communities residing in roots are diverse, some including non – pathogenic B. cereus group, and spp of Enterobacter, Pseudomonas, Cronobacter , with those close to water having the greatest diversity ( Sun et al, 2019 ).…”
Section: Rootssupporting
confidence: 83%
“…Similar to PGPM, co-inoculants also promote plant growth by improving soil nutrient availability, secreting hormones, changing the soil microbial community, and antagonizing ( Olenska et al, 2020 ; Kong and Liu, 2022 ; Luo et al, 2022 ). Some studies have shown that co-inoculants can promote the absorption of nutrients by crops, improve soil enzyme activity, and/or change the structure of the microbial community while promoting the growth of crops ( Hu et al, 2017 ; Moreira et al, 2020 ; Neemisha et al, 2022 ; Sarathambal et al, 2022 ). However, most of these are in vitro studies, and the primary mechanism by which inoculants promotes crop growth in the complex soil systems is still unclear.…”
Section: Introductionmentioning
confidence: 99%